Pelatihan Penerapan Alat Peraga Berbasis STEM Untuk Meningkatkan Sikap Ilmiah Siswa di SMP Negeri 1 Aikmel Lombok Timur - I Wayan Gunada; Ahmad Busyairi; Syahrial Ayub (Universitas Mataram, 2023)
This activity aims to improve students' scientific attitudes by conducting training on the application of STEM-based teaching aids. This activity was carried out at Aikmel Public Middle School 1 East Lombok, West Nusa Tenggara on Saturday 3 December 2022. The participants in this activity were class IV students, totaling 38 people. This activity is generally carried out in 2 (two) stages, namely the preparation stage and the implementation stage. In the preparatory stage, the preparation of teaching materials, teaching aids, and observation sheets was carried out and consolidated with the school. The implementation stage generally involves delivering material by utilizing teaching materials and teaching aids that have been prepared previously. This training activity went well in accordance with the expected goals and received a positive response from the partner schools. Based on the results of observations during the activity, it appears that STEM-based visual aids can stimulate students' scientific attitudes. This can be observed from the attitude of curiosity, objective attitude towards data/facts, open-minded attitude, critical thinking attitude, and student cooperation attitude.